Cinematography. Common to more than one film gauge. Image areas. Specification for dimensions and locations of the maximum permissible area for subtitles on 35 mm and 16 mm motion-picture release prints Part 5.2.1, (31st July 1987) - British Standards Institution,
No abstract available